P-B25 Influence of spirituality and modesty on acceptance of self sampling for cervical cancer screening. (January 2016) - Dareng, Eileen; Jedy-Agba, Elima; Bamisaye, Patience; Isa Modibbo, Fatima; Oyeneyin, Lawal; Adewole, Ayodele; Olaniyan, Olayinka; Dakum, Patrick; Pharoah, Paul; Adebamowo, Clement
Abstract : Introduction: Whereas systematic screening programs have reduced the incidence of cervical cancer in developed countries, the incidence remains high in developing countries. Among several barriers to uptake of cervical cancer screening, the roles of religious and cultural factors such as modesty have been poorly studied. Knowledge about these factors is important because of the potential to overcome them using strategies such as self-collection of cervico-vaginal samples. In this study we evaluate the influence of spirituality and modesty on the acceptance of self-sampling for cervical cancer screening. Methodology: We enrolled 600 participants in Nigeria between August and October 2014 and collected information on spirituality and modesty using 2 scales. We used principal component analysis to extract scores for spirituality and modesty and logistic regression models to evaluate the association between spirituality, modesty and preference for self-sampling. All analyses were performed using STATA 12. Results: Some 581 (97%) women had complete data for analysis. Most (69%) were married, 50% were Christian and 44% were from the south western part of Nigeria. Overall, 19% (110/581) of the women preferred self-sampling to being sampled by a health care provider. Adjusting for age and socioeconomic status, spirituality, religious affiliation and geographic location were significantly associated with preference for self-sampling, while modesty was not significantly associated. The multivariable OR (95% CI, P -value) for association with self-sampling were 0.88 (0.78 to 0.99, 0.03) for spirituality, 1.69 (1.09 to 2.64, 0.02) for religious affiliation and 0.96 (0.86 to 1.08, 0.51) for modesty. Conclusions: Our results show the importance of taking cultural and religious beliefs and practices into consideration in planning health interventions like cervical cancer screening. To succeed, public health interventions and the education to promote it must be related to the target population and its preferences.